2015
DOI: 10.5551/jat.26328
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Remnant Lipoprotein on Coronary Plaque Components

Abstract: Aim: Intravascular ultrasound (IVUS) is a useful modality for visualizing atherosclerotic lesions in coronary arteries, not only for the degree of arterial luminal stenosis but also for the plaque composition within the vessel walls. We aimed to determine the relationship between the clinical parameters and coronary plaque characteristics evaluated by IVUS in patients with stable angina under medical treatment. Methods: Plaque measurements within the coronary arteries were collected by coronary angiography and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
(45 reference statements)
1
13
0
Order By: Relevance
“…We have shown that adiponectin can switch macrophage polarization towards an anti-inflammatory phenotype 43) . Macronant lipoprotein levels, which are linked with coronary plaque vulnerability 13,14) . It has also been shown that high plasma adiponectin levels are associated with a reduced risk of myocardial infarction in healthy men 15) and CAD in diabetic men 16) .…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that adiponectin can switch macrophage polarization towards an anti-inflammatory phenotype 43) . Macronant lipoprotein levels, which are linked with coronary plaque vulnerability 13,14) . It has also been shown that high plasma adiponectin levels are associated with a reduced risk of myocardial infarction in healthy men 15) and CAD in diabetic men 16) .…”
Section: Introductionmentioning
confidence: 99%
“…Only 8 months of follow-up and relatively low dose of statin therapy did not decrease the necrotic-core and fibro-fatty components in the present study. As reported by a previous study 31) , the amount of necrotic-core or fibro-fatty components may be associated with remnant lipoprotein or with lipoproteins other than LDL-C and HDL-C. It may be another explanation that cholesterol-lowering therapy with statin did not decrease necrotic-core and fibro-fatty components.…”
Section: Discussionmentioning
confidence: 50%
“…RemL-C is a quantitative marker for the accumulation of remnant lipoproteins, and considered useful for analyzing cardiovascular risk in patients with accumulation of remnant lipoproteins [27,28]. In addition, elevated serum RemL-C levels are associated with coronary plaque vulnerability in patients with stable angina [29], and are useful predictors of postprandial dyslipidemia in young healthy individuals [30]. The administration of Omega-3 may therefore help reduce these residual cardiovascular risk factors in patients with dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%